Dose of Alcohol From Beer Required for Acute Reduction in Arterial Stiffness - Nishiwaki, Masato; Yamaguchi, Takahiro; Nishida, Ren; Matsumoto, Naoyuki (Frontiers in Physiology, 2020)
Acute beer or alcohol ingestion reduces arterial stiffness, but the dose required to reduce arterial stiffness is unclear. Therefore, this study aimed to determine the acute effects of ingesting various amounts of beer on arterial stiffness in healthy men. Nine men (20-22 years) participated, in eight trials in random order on different days. The participants each consumed 25, 50, 100, or 200 mL of alcohol-free beer (AFB25, AFB50, AFB100 and AFB200) or regular beer (B25, B50, B100, and B200), and were monitored for 60 min thereafter. Arterial stiffness did not significantly change among all AFB and B25. However, B50, B100, and B200 caused a significant decrease in arterial stiffness for approximately 30-60 min: heart-brachial pulse wave velocity (B50: -4.5 ± 2.4%; B100: -3.4 ± 1.3%; B200: -8.1 ± 2.6%); brachial-ankle pulse wave velocity (B50: -0.6 ± 2.0%; B100: -3.3 ± 1.1%; B200: -9.3 ± 3.0%); heart-ankle pulse wave velocity (B50: -3.7 ± 0.3%; B100: -3.3 ± 0.9%; B200: -8.1 ± 2.7%); and cardio-ankle vascular index (B50: -4.6 ± 1.3%; B100: -5.6 ± 0.8%; B200: -10.3 ± 3.1%). Positive control alcoholic beverages reduced arterial stiffness, and these reductions did not significantly differ regardless of the type of beverage. Our data show that consuming about 50 mL of beer can start to reduce arterial stiffness, and that the reduced arterial stiffness is mainly attributable to the alcohol in beer.